Hyperpersonal Communication in Sexual Fantasies: A Study on Users of Paid Video Call Sex Services in Indonesia - Tristi, Muhammad Alzaki; Arymami, Dian (Universitas Gadjah Mada, 2024)
The virtual era has redefined intimacy, with virtual platforms becoming a medium for fulfilling sexual desires in tangible ways. This article examines how hyperpersonal communication leverages Computer-Mediated Communication (CMC) technologies to facilitate sexual fantasies through paid Video Call Sex (VCS) services in Indonesia. Grounded in theories of Hyperpersonal Communication, Fetishism, Media Equation, and Cyberculture, this study analyzes how virtual media's technological affordances and communication processes enable the realization of sexual fantasies. Paid VCS services, as a form of cybersex, represent a convergence of economic motives and the pursuit of intimate satisfaction. Operating through instant messaging applications equipped with video and audio capabilities, these services have emerged as a digital avenue for sexual transactions. Using a qualitative descriptive approach with five online participants, this research highlights the intricate communication dynamics between users and service providers, focusing on the negotiation processes that shape and accommodate personalized sexual fantasies. These findings contribute to understanding how hyperpersonal communication unfolds in the context of virtual sexual interactions, revealing the interplay of technology, intimacy, and economic motives in contemporary digital culture